Gambaran Pengetahuan dan Sikap Remaja tenteng HIV/AIDS si Pondok Pesantren Assulami Lombok Barat - Suprayitna, Marthilda; Fatmawati, Baiq Ruli; Albayani, Melati Inayati (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2020)
HIV stands for Human Immuno deficiency Virus, which is a virus that can weaken immunity on humans. Meanwhile, AIDS stands for Acquired Immune Deficiency Syndrome, which is a collection of symptoms and infections or commonly called syndromes caused by damage to the human immune system due to the HIV virus. HIV / AIDS is a sexually transmitted disease that can causes of death. Adolescents are risk group for HIV / AIDS transmission. Proper knowledge on disease will help them to take prevention efforts. Adolescents promiscuity is a indicator that can transmit the disease. The aim of this research was to identify an overview of adolescent knowledge on HIV / AIDS. The research method used in this research was descriptive research. The populations of this research were 134 students, samples of the research were 57 people. The sampling technique used in this research was random sampling, Instrument of data collection used in this research was questionnaire. This research conducted at Assulamy Langko Islamic Boarding School, West Lombok. The results of this research obtained that more than 30 respondents were female (53%) and 27 respondents (42%) were male. The knowledge of students on HIV / AIDS was 44 respondents (77%) with sufficient criteria, and 13 respondents (23%) were lacking. It can be concluded that the knowledge of adolescents on HIV / AIDS in Assulamy Langko Islamic Boarding School is sufficient. Adolescents have good enough knowledge, but it needs to be considered and improved through providing health education related to HIV / AIDS